Compliance with Mandatory Environmental Reporting in Financial Statements: The Case of Spain (2001–2003) - Criado-Jiménez, Irene (Journal of business ethics, 2008)
Corporate, Social, Ethical and Environmental Reporting (SEER) should ideally discharge the accountability of an organisation to its stakeholders. Voluntary reporting has been characterised by a dearth of neutral and objective information such that the advocates of SEER recommend that it be made compulsory. Their underlying rationale is that legally specified disclosure requirements and enforcement mechanisms will enhance the quality of such reporting. This paper sets out to explore how realistic this scenario actually is, in view of the conflicting interpretations in the literature on this subject. To that end, a survey of the reporting patterns of 78 of the largest Spanish companies between 2001 and 2003 examines the extent of their compliance with the ICAC-2002 standard, which obliged them to make environmental disclosures in their financial statements. The results suggest that progressive and improved regulation could increase the volume and quality of SEER disclosures. They also suggest, however, that persistent non-compliance means that the problems associated with voluntary disclosure still exist. Finally, through an impression management perspective, the study reveals, the diverse strategies, ranging from dismissal to concealment, that are employed by companies to avoid transparency. As regulation improves and enforcement expectations rise, it becomes more difficult to dismiss compulsory reporting norms. As a result, some firms engage in more complex concealment strategies to attain corporate legitimacy, depriving stakeholders of regulatory information. The latter point serves to reconcile apparently contradictory explanations in the literature as to whether legitimacy theory might explain partial compliance with SEER regulation.